Review of the Neotropical blackfly subgenus Chirostilbia Enderlein (Diptera: Simuliidae) based on adults and pupal morphology - Hernandez, Luis Miguel; Shelley, Anthony John; de Luna Dias, Antonio Paulino Andrade; Maia-Herzog, Marilza (Zootaxa, 2008)
The species of the subgenus Chirostilbia are reviewed based on the adult and pupal morphology. All main taxonomic characters are fully illustrated with colour digital images and keys for species identification are given. Taxonomic discussions for each species and summaries of their distribution and biology are also provided. Thirteen species are now considered to be valid in the subgenus Chirostilbia. Since they are similar morphologically no separation into species groupshas been attempted. Lectotypes are designated for the following species: S. distinctum Lutz and Trichodagmia lutziana Enderlein [= S. pertinax Kollar]. Simulium nilesi Rambajan is transferred from its synonymy with S. perflavum Roubaud in the subgenus Psilopelmia Enderlein to Chirostilbia as a junior synonym of S. subpallidum Lutz. The thoracic pattern of the male of S. empascae is described and illustrated for the first time.